- Thread starter idontknow
- Start date

2+3 = 5

2-3 = -1

4+2 = 6

4 -2 = 2

7 +11 = 18

7 - 11 = -4

so it looks like our rule is:

if a +b = m

a -b = m -2b

Doubtful. Example: m=0, then a+b=0. As a result let a=x thus b=-x so a-b=2x, where x can be any number. So f(m)=2x, not at all defined.If \(\displaystyle a+b=m\) , express \(\displaystyle a-b\) in terms ofm.

\(\displaystyle a-b=f(m)=?

\)

Or, in symbols:If \(\displaystyle a+b=m\) , express \(\displaystyle a-b\) in terms ofm.

\(\displaystyle a-b=f(m)=\)?

a + b = m

a - b = a + (b - 2b) = (a + b) - 2b = m - 2b

-Dan